Transformative communication - Malay, Renato Benigno; Alzona, Sandra Soraya (Quezon City, Philippines : Megabooks Co., 2006)
Communication is inevitable and all of creations are in constant touch with each other. Humanity is not always aware of how this dialogue happens. It is not only a possibility, it is so that this exchange will happen. That is the beauty of life, that prayers will be answered, which expectations met make life more meaningful and emphasize that, since we are in constant communication, we can choose what we want to say that we may even be unaware of. Disease is one good example of something that is "communicable." For good or ill, we are contagious. We know what we communicate consciously, but for the most part people do so by default. While there is an element of mystery in ourselves, we are so much a part of each other that we will surely affect the whole. Therein lies the opportunity. And this book aims to bring to the fore that communicator, who remains in the fringes, if only to explore the potential in each of us.
Part 1. The Old order -- Part 2. The New order -- Part 3. The Transformative -- 20 Qualities of a transformative communicator.
Keywords: COMMUNICATION SOCIAL ASPECTS